Cellular RNA and DNA sensing pathways are essential for the dose-dependent response of human monocytes to ionizing radiation - Mikhalkevich, Natallia; Russ, Eric; Iordanskiy, Sergey (Frontiers in Immunology, 2023)
Circulating monocytes are important players of the inflammatory response to ionizing radiation (IR). These immune cells migrate to radiation-damaged tissues and differentiate into macrophages that phagocytize dying cells, but also facilitate inflammation. Besides the effect of damage-associated molecular patterns, released from irradiated tissues, the inflammatory activation of monocytes and macrophages is largely dependent on IR-induced DNA damage and aberrant transcriptional activity, which may facilitate expression of type I interferons (IFN-I) and numerous inflammation-related genes. We analyzed the accumulation of dsRNA, dsDNA fragments, and RNA:DNA hybrids in the context of induction of RNA-triggered MAVS-mediated and DNA-triggered STING-mediated signaling pathways, in primary human monocytes and a monocytic cell line, THP1, in response to various doses of gamma IR. We found that exposure to lower doses (<7.5Gy) led to the accumulation of dsRNA, along with dsDNA and RNA:DNA hybrids and activated both MAVS and STING pathway-induced gene expression and signaling activity of IFN-I. Higher doses of IR resulted in the reduced dsRNA level, degradation of RNA-sensing mediators involved in MAVS signaling and coincided with increased accumulation of dsDNA and RNA:DNA hybrids that correlated with elevated STING signaling and NF-κB-dependent gene expression. While both pathways activate IFN-I expression, using MAVS- and STING-knockout THP1 cells, we identified differences in the spectra of interferon-stimulated genes (ISGs) that are associated with each specific signaling pathway and outlined a large group of STING signaling-associated genes. Using the RNAi technique, we found that increasing the dose of IR activates STING signaling through the DNA sensor cGAS, along with suppression of the DDX41 helicase, which is known to reduce the accumulation of RNA:DNA hybrids and thereby limit cGAS/STING signaling activity. Together, these results indicate that depending on the applied dose, IR leads to the activation of either dsRNA-induced MAVS signaling, which predominantly leads to the expression of both pro- and anti-inflammatory markers, or dsDNA-induced STING signaling that contributes to pro-inflammatory activation of the cells. While RNA:DNA hybrids boost both MAVS- and STING-mediated signaling pathways, these structures being accumulated upon high IR doses promote type I interferon expression and appear to be potent enhancers of radiation dose-dependent pro-inflammatory activation of monocytes.